Apoio remoto à saúde: estudo com método netnográfico e análise de tendências para pacientes crônicos online. perspectivas interativas, de vínculos pessoais e um olhar para fibromialgia - Moretti, Felipe Azevedo [UNIFESP] (2018)
Objectives: The current research analyzes the personal profile, interests, interactive behaviors and interpersonal relationships of patients with chronic diseases in online health settings. It also investigate the forms of social support perceived by participants from virtual support groups, with a central focus on fibromyalgia. In addition, the study investigates new opportunities for remote support for chronic diseases that stimulate adherence to treatments. Methodology: Qualitative and quantitative research methods were combined. Initially, we analyzed specific responses on interactional patterns of behavior of 1,828 people attending online health platforms. Regarding the fibromyalgia research, a participatory netnography was conducted in which a Facebook community with 8,197 members was monitored for 6 months with weekly records of activities and behaviors. In addition, an electronic survey was distributed to the community members comprised of a validated social support satisfaction scale (ESSS) and questions about contentment with activities offered, criticisms, and suggestions for improvements to these groups. To identify new possibilities of remote support that stimulated adherence to treatments, 107 interviews were conducted with specialists in medical informatics and in the management of chronic patients. Other online questionnaires and patient interviews were used in some phases of the research. Results: Virtual health support platforms proved to be resources frequently used by chronic patients and such users usually see value in the possibility of exchanging experiences from the disease. Responses from the female gender predominated in the investigations. Variables such as schooling, age and income interfered in the way patients relate to health decision making (p <0.004). The behavior of searching health information for oneself or for family members, interaction with doctors or professionals after online searches, mutual help in virtual communities, and a broad sharing of personal data in discussion groups are frequent attitudes among the patients investigated. In the fibromyalgia group new treatments and patient rights are among the topics of greatest interest. The specific fibromyalgia community of the netnography has shown to have social relevance and impact on the life of its members, but presents difficulties of engagement and generation of interpersonal bond among the users. The electronic social support survey applied had 444 patients respondents and 72.1% (320) claimed to have made no significant friendships in the group. However, despite a few friendships created, most respondents (> 60%) miss a lot someone truly intimate to be able to talk, and approximately 70% misses a lot social activities. Conclusion: It is considered strategic to expand remote support initiatives that enhance interpersonal ties and social support in future online programs for chronic patients.